V. Cartoons and sketches, - Duggan, Éamonn, 1874-1936
Humorous cartoons and sketches, produced in pen and ink and compiled by the Cumann na nGaedhael politician Éamonn Duggan. The artists' identity is only indicated on one of the five sketches.